ANALISIS PEMBELIAN PRODUK BARU YANG TIDAK DIRENCANAKAN PADA TOKO ONLINE - Nugraha, Wahyu Fitrayanto; Sumarsono, Sumarsono (Performance, 2012)
This study analyzed the replication of unplanned purchases at online stores that exist in the kaskus.us fjb seen from the intentions and consumers of psychological factors as a stimulus, a case study at 77 kaskus.us fjb users. This study uses new variable product knowledge, consumer's esteem, consumer's excitement, e-wom, on impulse buying intention and impulse buying behavior. The study revealed that; new product knowledge and consumer's excitement to have a positive relationship to impulse buying intention. Note also that the new product knowledge, consumer's esteem, and word of mouth have a positive relationship to impulse buying behavior. And also found that a positive relationship to impulse buying on impulse buying behavior intention.